Challenging the obesity paradox: extreme obesity and COPD mortality in the SUMMIT trial. Issue 3 (26th July 2021) - Brigham, Emily P.; Anderson, Julie A.; Brook, Robert D.; Calverley, Peter M.A.; Celli, Bartolome R.; Cowans, Nicholas J.; Crim, Courtney; Diserens, James E.; Martinez, Fernando J.; McCormack, Meredith C.; Newby, David E.; Yates, Julie; et al.
Populations with COPD demonstrate higher survival in overweight and obese compared with normal weight; the "obesity paradox". Relationships in less-severe COPD are unclear, as is the impact of cardiovascular risk, and few studies include individuals at extremes of obesity. We examined the relationship between body mass index (BMI; defined as underweight: <20 kg·m −2, normal: 20–25 kg·m −2, overweight: 25– <30 kg·m −2, obese class I: 30– <35 kg·m −2, class II: 35– <40 kg·m −2 and class III: ≥40 kg·m −2 ), morbidity, and mortality in the SUMMIT trial population (n=16 485), characterised by moderate COPD and heightened cardiovascular risk with a substantial proportion with class III obesity. The association between BMI category and time to event was modelled via proportional hazards (reference normal weight) adjusted for demographics and cardiorespiratory disease. Consistent with the paradox, underweight individuals demonstrated higher mortality (hazard ratio (HR) 1.31 (95% CI 1.04–1.64)), with lower mortality among overweight (HR 0.62 (95% CI 0.52–0.73)) and obese class I (HR 0.75 (95% CI 0.62–0.90)). However, mortality increased in obese class III (HR 1.36 (95% CI 1.00–1.86)). Death was primarily attributable to cardiovascular causes. Within a large, multinational cohort with moderate COPD and increased cardiovascular risk, the phenomenon of reduced mortality with obesity did not persist at BMI >40 kg·m −2, suggesting that obesity may not remain protective at the extremes in this population. In a population with moderate COPD, at heightened cardiovascular risk and containing a substantial proportion of individuals with BMI ≥40 kg/m 2, BMI and mortality demonstrate a U-shaped (rather than J-shaped) relationship https://bit.ly/3hDztI6